2012
DOI: 10.3390/cancers4010193
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Antigens for Specific Immunotherapy of Prostate Cancer

Abstract: Prostate cancer (PCa) is the most common noncutaneous cancer diagnosis and the second leading cause of cancer-related deaths among men in the United States. Effective treatment modalities for advanced metastatic PCa are limited. Immunotherapeutic strategies based on T cells and antibodies represent interesting approaches to prevent progression from localized to advanced PCa and to improve survival outcomes for patients with advanced disease. CD8+ cytotoxic T lymphocytes (CTLs) efficiently recognize and destroy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 166 publications
0
45
1
1
Order By: Relevance
“…Among all PC cell surface proteins (prostate stem cell antigen, prostein, T cell receptor gamma alternate reading frame protein, six-transmembrane epithelial antigen of the prostate 1, and PSMA), PSMA is a cell-surface protein that is highly overexpressed in almost all prostate cancers and within the tumor neovasculature of other solid tumors [28]. Moreover, FDA-approved anti-PSMA antibody is a prostate-specific imaging agent and a target for the delivery of PC therapeutic agents [29, 30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all PC cell surface proteins (prostate stem cell antigen, prostein, T cell receptor gamma alternate reading frame protein, six-transmembrane epithelial antigen of the prostate 1, and PSMA), PSMA is a cell-surface protein that is highly overexpressed in almost all prostate cancers and within the tumor neovasculature of other solid tumors [28]. Moreover, FDA-approved anti-PSMA antibody is a prostate-specific imaging agent and a target for the delivery of PC therapeutic agents [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Among many cell-surface protein markers, prostate specific membrane antigen (PSMA) is highly overexpressed in prostate cancers [28], and thus it is considered a valid target for PC [29, 30]. In addition, anti-PSMA antibody or PSMA-specific aptamers A10-3.2 aptamer based targeting and imaging have been tested on patients with PC [29, 31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of candidate TAAs have been identified in various human cancer types [8], including liver cancer, breast cancer [9], prostate cancer [10], ovarian cancer [11], renal cancer [12], head and neck cancer [13], esophageal cancer [14], lymphoma [15], gastric cancer [16]and leukemia [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the low mutational burden of prostate cancer limits the immunogenicity of the tumor [9]. Prostate cancer does, however have many public tissue-associated antigens, including PSA, PMSA, prostatic alkaline phosphatase (the target of sipuleucel-T) and NY-ESO, and there are a variety of Phase I studies examining the potential to target these antigens to elicit an immune response [10]. It is increasingly recognized that tumors undergo a process of adaptive immunoediting which allows the selection and outgrowth of subclones that can grow in an immunocompetent host [11].…”
Section: Biological Basis For Immunotherapy In Prostate Cancermentioning
confidence: 99%